Novel and innovative approaches for treatment of β-thalassemia - Sandeep Soni, MD (Elsevier, 2017)
Basic science studies have provided new insights into the pathophysiology of β-thalassemias. Studies of genotypic and phenotypic heterogeneity among patients and better understanding of control of erythropoiesis have provided new targets for designing novel agents that can be tailored to individual patient needs. JAK-2 kinase inhibitors and agents targeting the GDF-11/SMAD pathway are in clinical trials. Recent understanding of the control of switch of HbF to HbA during infancy has provided new targets for development of drugs and gene-editing strategies. Advancement in vector design, purification and transduction of human stem cells have led to multiple gene therapy clinical trials that are exploring the clinical benefits, safety and durability of these approaches. HSCT remains the only curative approach at present and continued improvements in unrelated and haplo-identical transplants is helping to expand the donor pool. Even though the future looks promising, carefully designed clinical trials in adults and children, with suitable end-points are still needed to confirm the efficacy, toxicity of these new agents, and improvements in quality of life of patients with β-thalassemia.